Complete Maya programming. Vol. II an in-depth guide to 3D fundamentals, geometry, and modeling - Gould, David A. D. (San Francisco, CA : Morgan Kaufmann Publishers, 2005)
David Gould's acclaimed first book, Complete Maya Programming: An Extensive Guide to MEL and the C++ API, provides artists and programmers with a deep understanding of the way Maya works and how it can be enhanced and customized through programming. In his new book David offers a gentle, intuitive introduction to the core ideas of computer graphics. Each concept is explained progressively and is fully implemented in both MEL and C++ so that an artist or programmer can use the source code directly in their own programs. Geometry and modeling are covered in detail with progressively more complex examples demonstrating all of Maya's possible programming features. David Gould's first volume is widely regarded as the most authoritative reference on Maya programming. Volume II continues this tradition and provides an unmatched guide for the artist and programmer tackling complex tasks. * Covers a spectrum of topics in computer graphics including points and vectors, rotations, transformations, curves and surfaces (polygonal, NURBS, subdivision), and modeling. * Offers insights to Maya's inner workings so that an artist or programmer can design and develop customized tools and solutions. * Discusses problem solving with MEL (Maya's scripting language) and the more powerful and versatile C++ API, with plenty of code examples for each.
Preface; 1 Introduction; 2 Points; 3 Vectors; 4 Rotations; 5 Transformations; 6 Transform Nodes; 7 Coordinate Frames; 8 Polygonal Meshes; 9 Nurbs; 10 Subdivision Surfaces; 11 Contexts (Tools); A Further Learning; B Further Reading; Glossary; Index.
Includes bibliographical references (p. 687-689) and index.
Keywords: Maya (Computer file); Three-dimensional display systems; Computer animation; Computer graphics; C++ (Computer program language); Electronic books